Numerical study of jet impingement cooling on a smooth curve surface - Hayder, Ali Mohammed (2014)
Impinging jets are a best method of achieving particularly high heat transfer coefficient and are therefore employed in many engineering applications. In this study we seek to understand the mechanism of the distributed heat on the curve surface with the goal of identifying preferred methods to predicting jet performance. The goals that have been achieved in the numerical results displayed are determine the influence of impingement jet characteristics on thermal and flow field on a curve surface, determine the variation of Nusselt numbers (NuD) along the curve surface in order to understand the heat transfer characteristics and study the effect of position (in the center, in the mid and in the end) and angle (α=90°, 60° and 30°) of jet impingement on curve surface, different Reynolds numbers (ReD) in range of (5000, 6000, 7000, 8000 and 9000). The program, which was extracted results it is (GAMBIT 2.4.6) and (FLUENT 6.3), simulation is (2-D) in submerged jet flow and the continuity, momentum and energy equations were solved by means of a finite volume method (FVM). This study covers the effect of different Reynolds numbers (ReD) on average Nusselt numbers (Nuavg) and local Nusselt numbers (NuD). From the result, the average Nusselt numbers (Nuavg) increased with the increase of Reynolds numbers (ReD) for all cases, in comparison between different positions (center, mid and end), of nozzle on curve surface at angle (α=90°) the maximum value of average Nusselt numbers (Nuavg=388.3) is found when the nozzle locate in the end followed by the mid position and smallest value of average Nusselt numbers (Nuavg=182.25) in the center of curve surface. In case of slant angle (α=60º) the maximum value of average Nusselt numbers (Nuavg=387.47) is found when the nozzle locate in the end followed by the mid position and smallest value of average Nusselt numbers (Nuavg=308.3) in the center of curve surface.